Network pharmacology and molecular docking study for biological pathway detection of cytotoxicity of the yellow jasmine flowers - Seham S. El-Hawary; Marzough A Albalawi; Ayat O. S. Montasser; Shaimaa R. Ahmed; Sumera Qasim; Ali A. Shati; Mohammad Y. Alfaifi; Serag Eldin I. Elbehairi; Omnia F. Hassan; Abdelfattah A. Sadakah; Fatma A. Mokhtar (BMC, 2023)
Abstract Background The yellow jasmine flower (Jasminum humile L.) is a fragrant plant belonging to the Oleaceae family with promising phytoconstituents and interesting medicinal uses. The purpose of this study was to characterize the plant metabolome to identify the potential bioactive agents with cytotoxic effects and the underlying mechanism of cytotoxic activity. Methods First, HPLC-PDA-MS/MS was used to identify the potential bioactive compounds in the flowers. Furthermore, we assessed the cytotoxic activity of the flower extract against breast cancer (MCF-7) cell line using MTT assay followed by the cell cycle, DNA-flow cytometry, and Annexin V-FITC analyses alongside the effect on reactive oxygen species (ROS). Finally, Network pharmacology followed by a molecular docking study was performed to predict the pathways involved in anti-breast cancer activity. Results HPLC-PDA-MS/MS tentatively identified 33 compounds, mainly secoiridoids. J. humile extract showed a cytotoxic effect on MCF-7 breast cancer cell line with IC50 value of 9.3 ± 1.2 µg/mL. Studying the apoptotic effect of J. humile extract revealed that it disrupts G2/M phase in the cell cycle, increases the percentage of early and late apoptosis in Annexin V-FTIC, and affects the oxidative stress markers (CAT, SOD, and GSH-R). Network analysis revealed that out of 33 compounds, 24 displayed interaction with 52 human target genes. Relationship between compounds, target genes, and pathways revealed that J. humile exerts its effect on breast cancer by altering, Estrogen signaling pathway, HER2, and EGFR overexpression. To further verify the results of network pharmacology, molecular docking was performed with the five key compounds and the topmost target, EGFR. The results of molecular docking were consistent with those of network pharmacology. Conclusion Our findings suggest that J. humile suppresses breast cancer proliferation and induces cell cycle arrest and apoptosis partly by EGFR signaling pathway, highlighting J. humile as a potential therapeutic candidate against breast cancer.